Compliance of audit requirements by public listed companies in Malaysia capital markets - Sweity, Rami M A (2017)
Purpose - In recent years, the corporate governance has become a subject of concern by many stakeholders and emphasis has been laid on the roles of Audit Committees to ensure the quality of financial reporting and compliance of audit requirements by the public listed companies (PLCs).Over the years poor corporate governance (CG) has been widely and frequently reported as a major factor that led to the 1997 Asian crisis, and numerous organisations have claimed that it was the main cause indeed (Nam, 2004).The World Bank claimed that poor CG within the Eastern Asian countries is attributed to a lack of an effective board of directors, inadequate internal control, unreliable financial statements, absence of sufficient information, poor compliance, and a lack of effective audit system (World Bank, 1998).The challenges mentioned have led to huge losses and poorly estimated liabilities.However, the regulatory bodies in charge of monitoring as well as controlling the affairs have failed to identify these weaknesses and to put in corrective measures.Malaysia was also hard hit by the Asian economic crisis that impacted the region in 1997.Corporate sector weaknesses and poor CG were considered important causes of the crisis (Khatri, Leruth & Piesse, 2002).The companies affected were in financial distress and had to seek protection under a winding up/bankruptcy protection.According Abdul Rahman et al (2007), as a result of the advents of the meltdown, the government of Malaysia saw the need to keep the standard of CG in all companies to regain and re-secure investors’ interest and confidence.As a result, the Malaysian Code of Corporate Governance (MCCG) is introduced (HLFC, 2000) and the Bursa Malaysia strengthen their Listing Requirements and best practice efforts is been practised in PLCs.One of the principles in the MCCG, Bursa Malaysia Listing Requirements is concerning the requirements of audit practises among the PLCs.In light of the above discussion, this paper focuses on the issue of compliance of audit requirements by the PLCs in Malaysia Capital Markets.